Foraging of a hypogaeic army ant: a long neglected majority - Hashim, Rosli; Maschwitz, U.; Berghoff, S.M.; Weissflog, A.; Linsenmair, K.E. (2002)
Army ants have been studied thoroughly for more than a century. The conduction of column and swarm mass raids, featured by epigacicly active species, is believed to be a central characteristic of army ant behavior. Most army ant species, however, lead a hypogaeic life. Due to the difficulties to observe them, nothing is known about their hypogacic behavior in the field. Using palm oil baits, trail excavations, and laboratory observations, the hypogaeic foraging of Dorylus (Dichthadia) laevigatus was observed in Malaysia. D. laevigatus was found to construct stable hypogaeic trunk trail systems providing quick and easy access to all parts of its foraging area. Small column raids were conducted throughout the ground stratum and above the ground surface. These raids were caste specific, with the smallest workers predominantly following existing cracks and tunnels in the soil. In case of food location, larger workers were recruited from nearby trunk trails. Exploratory trails leading to prey had to be widened before larger workers could gain access and help to process the food. Bulky food sources such as baits or termite mounds could be exploited over several weeks to months. Besides raiding in columns, D. laevigatus came occasionally to the ground surface at night to conduct swarm raids. This combination of swarm and column raids with the use of trunk trails has never been demonstrated for a classical army ant species. The omnipresence of D. laevigatus within its foraging area stands in sharp contrast to epigaeicly active species, characterized by a very localized and temporary presence at foraging sites. D. laevigatus stayed in the same foraging area for several weeks to months. Having a broad diet and the ability to exploit bulky food sources over long periods of time, D. laevigatus seems to follow a sustainable use of the soil fauna. Summing up these particularities demonstrates a remarkable divergence of the hypogacic foraging of D. laevigatus from that of epigacicly foraging army ant species.